Poligami Menurut Pandangan Kader Wahdah Islamiyah Ternate, Maluku Utara. - Umar, Rafli; Abbas, Abd. Haris; Abubakar, Fatum (Maqasid: Jurnal Studi Hukum Islam, 2025)
Polygamy, both in Islamic thought and modern social reality, has always been a controversial topic and remains a subject of interest and debate. Although it has legal and theological foundations, polygamy continues to be contentious, especially when practiced outside the prescribed regulations. This study uses a descriptive qualitative approach to explore in depth the perspectives of Wahdah Islamiyah Ternate cadres on polygamy. The primary data sources include interviews, observations, and documentation. The analysis is conducted through data reduction, presentation, and conclusion drawing. The study finds that, overall, polygamy among Wahdah Islamiyah Ternate cadres is viewed as a permissible option in Islam, with key conditions being justice, financial capability, responsibility, and official registration at the Office of Religious Affairs (KUA). Although some cadres view polygamy as a fundamental ruling, its practice must still be adapted to the social context, individual readiness, and national legal provisions. The majority agree that polygamy should not be practiced secretly (sirri), and when conducted properly, it can serve as a solution to marital problems, rather than merely fulfilling lustful desires. However, some cadres have engaged in unregistered polygamous marriages (sirri) without legal procedures, raising questions about their religious commitment and compliance with state laws. This inconsistency generates negative public perceptions and can tarnish the image of Islamic missionary organizations and Islam in general.   Keywords: Islamic Law, Maslahah (Public Interest), Polygamy, Wahdah Islamiyah Ternate.